A study on implementing promotion strategy in Kolej Yayasan Melaka / Nur’ain Saad - Saad, Nur’ain (Faculty of Business and Management, 2015)
Promotion is used to communicate with customers with respect to product offerings. Promotion has a key role in determining profitability and market success and is one of the key “Four Ps” of the marketing mix. The tools that can be employed in the promotional mix include: advertising; direct marketing; sales promotion; public relations and publicity; personal selling and sponsorship. The purpose of this study is to present implementation promotion strategy in Kolej Yayasan Melaka where the promotion strategy is one in marketing mix element and it’s important to company take as a marketing strategy for attract student study at Kolej Yayasan Melaka. The study is conceptual based on a review of academic literature on promotion strategy in major marketing journal. These study present selected references classified by key marketing strategy topic for further pursuit by interested readers. This study also reflects my experience and view based on practical training at Kolej Yayasan Melaka and trade journals.